BHUTTO’S BILATERALISM: ITS IMPORTANCE AND RELEVANCE IN MODERN INTERNATIONAL RELATIONS - Syeda Sajjal Zahra; Dr. Tahir Jamil (International Journal of Contemporary Issues in Social Sciences, 2024)
Bhutto's bilateralism is a concept that has gained significant importance in modern international relations. It refers to the approach adopted by former Pakistani Prime Minister Zulfikar Ali Bhutto in his foreign policy, which emphasized the importance of building strong and mutually beneficial relationships with other countries through bilateral agreements. This approach has become increasingly relevant in today's globalized world, where countries are interconnected and interdependent on each other for various economic, political, and security reasons. Therefore, the main aim of this research is to analyze his stance of counter security by launching nuclear project and to evaluate Bhutto’s policy in conducting relations with China and USSR based on bilateralism while using historical, descriptive, and analytical research methodology. One of the main reasons for the relevance of Bhutto's bilateralism in modern international relations is its emphasis on equality and mutual respect in relationships between nations. In today's world, where power dynamics and hegemony play a significant role in shaping global politics, Bhutto's approach offers a more balanced and fair way of conducting international relations. It promotes the idea of sovereignty and non-interference in the internal affairs of other countries, which is crucial in maintaining peace and stability. Additionally, Bhutto's emphasis on bilateralism also promotes the idea of mutual cooperation and understanding, which is essential in addressing global challenges such as climate change, terrorism, and economic inequality. Overall, Bhutto's bilateralism offers a more effective and sustainable way of conducting international relations in today's complex and interconnected world.